2003
DOI: 10.3989/scimar.2003.67s1337
|View full text |Cite
|
Sign up to set email alerts
|

A bioeconomic model for Mediterranean fisheries, the hake off Catalonia (western Mediterranean) as a case study

Abstract: SUMMARY:The theoretical aspects and the associated software of a bioeconomic model for Mediterranean fisheries are presented. The first objective of the model is to reproduce the bioeconomic conditions in which the fisheries occur. The model is, perforce, multispecies and multigear. The main management procedure is effort limitation. The model also incorporates the usual fishermen strategy of increasing efficiency to obtain increased fishing mortality while maintaining the nominal effort. This is modelled by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 9 publications
0
83
0
Order By: Relevance
“…takes place occasionally and opportunistically, but it is considered rather rare (Santojanni et al, 2005). The bioeconomic model called MEFISTO is a multispecies, multifleet and multigear simulation model described in detail in Lleonart et al (1999Lleonart et al ( , 2003. Starting from an initial condition, the simulation model incorporates the trajectory of resources and fishing fleets, disaggregated by vessels or homogeneous vessel classes, and computes the most probable future trajectory when some parameters in the model are changed, simulating management actions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…takes place occasionally and opportunistically, but it is considered rather rare (Santojanni et al, 2005). The bioeconomic model called MEFISTO is a multispecies, multifleet and multigear simulation model described in detail in Lleonart et al (1999Lleonart et al ( , 2003. Starting from an initial condition, the simulation model incorporates the trajectory of resources and fishing fleets, disaggregated by vessels or homogeneous vessel classes, and computes the most probable future trajectory when some parameters in the model are changed, simulating management actions.…”
Section: Methodsmentioning
confidence: 99%
“…The MEFISTO model has been previously applied to a case study of hake in Catalonia (western Mediterranean), as shown in Lleonart et al (2003), but it was later applied to red shrimp (Aristeus antennatus) fisheries in the Catalan sea and to carry out an analysis of hand-line and gillnet coastal fisheries of Pernambuco State (Mattos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Catalan and northern Tyrrhenian seas, recruits and juveniles are caught by bottom trawls, while the adult population, representing a percentage of between 37 and 46% of the total landings , is also caught with longlines and gillnets (Aldebert et al, 1993;Sbrana et al, 2007). In both study areas, as in many zones of the Mediterranean, growth overfishing can be assumed (the hake stock shows signals of growth overexploitation) (Aldebert et al, 1993;Aldebert and Recasens, 1996;Lleonart et al, 2003;FAO, 2005).…”
Section: Introductionmentioning
confidence: 99%